PENGARUH MEKANISME CORPORATE GOVERNANCE, FINANCIAL DISTRESS, DAN AUDIT TENURE TERHADAP INTEGRITAS LAPORAN KEUANGAN - Wulandari, Sri; Ermaya, Husnah Nur Laela; Mashuri, Ayunita Ajengtiyas Saputri (Jurnal Akunida, 2021)
This research is a quantitative research that aims to find out empirically the effect of independent commissioners, audit committees, financial distress, and audit tenure on the integrity of financial statements in manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample collected was 55 companies based on purposive sampling technique. Hypothesis testing using multiple linear regression analysis which is processed using SPSS version 25 program with a significance level of 5%. This study obtained the results that: (1) independent commissioners have no effect on the integrity of financial statements, (2) the audit committee has no effect on the integrity of financial statements, (3) financial distress has a significant negative effect on the integrity of financial statements, (4) audit tenure has a significant effect positive on the integrity of financial statements.